(3gOGjI GdQGei Edi GdBZQGV hGdeQGeis - (3GdMSf Hf eMeO Hf YjShf GdMfaj GdSfLGQjs ((3GdbGgQI s)
(3ChdgG (B:s
(3hHYO , abO PcQJ ai gPG GdcJGH NdGUI cdGe GdChdjf hGdBNQjf ef GdQeGI hGdeLGgOjf s
(3BNQgG (B:s
(3aGSJZf Hg Yf LejY GdcJH GdeUfaI ai gPG Gdaf , aEfg fJjLI YOI cJH cKjQg hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi GdfHi eMeO hCdg hUMHg s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B136 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B38 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs